Analysis of Carrying Capacity and Willingness to Pay Conservation Costs for Tourists in the Ciletuh-Palabuhanratu Geopark Area - Wahyuni, Sri; Mulatsih, Sri; Syartinilia (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
This study aimed to analyze the carrying capacity of Curug Cimarinjung and Puncak Darma using the Douglass method and the willingness to pay for conservation fees using the Contingent Valuation Method Respondents to the research were 150 tourists and several tourism managers. Curug Cimarinjung can accommodate as many as 184 people day-1 , and the Puncak Darma as many as 118 people day-1. Tourists who were willing to pay for conservation fees comprised 78% of the total respondents with a one-time payment mechanism through an entrance ticket. In total of 39.39% of respondents were not willing to pay as they believed that it was the responsibility of the government. The conservation costs were IDR 10,000 for Curug Cimarinjung and IDR 5,000 for Puncak Darma. The difference in conservation costs was because the attractiveness of the attractions in the two tourist spots varied, thus affecting the number of tourists and the nominal amount that tourists were willing to pay. If the tariff was adjusted according to the average Willingness to Pay, an entry fee at Cimarinjung Waterfall would have been charged, which was initially IDR 5,000 person-1, would have been IDR 15,000 person-1, while at Puncak Darma it would have been IDR 3,000 person-1 to IDR 8,000 person-1 . Determining ticket prices that had been adjusted to the average Willingness to Pay could control the number of visits so that they did not exceed capacity and did not disturb biodiversity conservation. In such conditions, tourists could carry out tourist activities comfortably and safely.